Designing Mandatory Pension Schemes : Some Lessons from Argentina, Chile, Malaysia, and Singapore - Vittas, Dimitri (World Bank, Washington, DC, 2012)
In most countries, participation in a public pension system involving some kind of redistribution is compulsory, while participation in private pension schemes is voluntary. There are growing fears in many countries that the value of public pensions will not be sustained. There are similar fears about company pensions. The credibility of company pensions depends on the integrity and solvency of large employers, which can no longer be taken for granted. These problems point to a need to refine compulsory saving. Drawing on the experiences of countries in Asia, Latin America, and elsewhere, this Note provides some guidance on answering the following questions: 1) Whom to compel? 2) Defined contribution or benefit? 3) How large should compulsory contributions be? 4) Who should manage the funds? 5) What types of regulation are appropriate? 6) What state guarantees for what system? 7) How to offer tax incentives?